PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA LARISSA AESTHETIC CENTER CABANG SALATIGA) - Fransisca Anugrahani; Sendhang Nurseto (Jurnal Ilmu Administrasi Bisnis, 2017)
Larissa Aesthetic Center is a beauty clinic with the theme “Back to Nature” and they growing so fast. However, these developments still can’t satisfy to the consumers. We can seen the fact from the high consumer complaints on the company. The purpose of doing research is to know the influence of product quality and service quality on the customer loyalty of consumers Larissa Aesthetic Center Branch Salatiga. The sample in this study amounted to 100 respondents using purposive sampling method. Analysis of the data in this study using a test validity, reliability, linear regression analysis, significance test and determination with SPSS 23. The result of this study indicate that have significantly influence about product quality to customer loyalty, service quality to customer loyalty, and product quality, service quality to customer loyalty. The suggestions for improving product quality and service quality on the product inovation and optimal service to improve customer loyalty.